PENGUATAN KARAKTER PEDULI LINGKUNGAN MELALUI MODEL CTL (CONTEXTUAL TEACHING AND LEARNING) BERBANTUAN ASSEMBLR EDU - Sudarmiani; Paryatin; Rahayu, Wiwit; Mujiastutik (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to improve students' environmental awareness using the Contextual Teaching and Learning (CTL) model supported by Assemblr Edu. Through the Classroom Action Research (CAR) method conducted in two cycles, this study links contextual materials with interactive digital media. The findings show a significant increase in students' environmental awareness from 67% in cycle I to 87% in cycle II, indicated by increased student awareness of cleanliness and ecosystems.